Analisis Kualitas Perairan Muara Sungai Dumai ditinjau dari Aspek Fisika, Kimia dan Biologi - Rena Dian Merian; Mubarak Mubarak; Sigit Sutikno (Universitas Riau, 2016)
River estuary water quality analysis from the aspects of physics, chemistry and biology. Physicsaspect measured were temperature, salinity, brightness and acidity (pH). Chemistry parametersare ammonia, nitrate and nitrite. While the biology aspect of the parametersanalyxed were phytoplankton abundance. Each parameters measuredat each station withamount 16 stations. The distance of station from estuary Dumai river to Rupat strait are 25 m, 50 m and 100 m.Sample of parameter measured taken at tide receded toward and tide towards the down.